EFFECTIVENESS OF IMPLEMENTATION OF CONCEPT ATTAINMENT LEARNING MODEL TO INCREASE COGNITIVE LEARNING OUTCOMES OF HIGH SCHOOL STUDENTS - Dina Purwanti; Azizahwati Azizahwati; Mitri Irianti (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2019)
This research aimed to determine the effectiveness of the implementation of concept attainment learning model to increase cognitive learning outcomes. The research method used is pre-experimental design with intact group comparison design. The research subjects were students of class XI SMA Negeri 9 Pekanbaru, in which class XI IPA4 was an experimental class and class XI IPA5 was a control class. The experimental class uses a concept attainment learning model and a control class with a conventional learning. The data was obtained from cognitive learning outcomes test which given to students after the learning process was carried out. Data were analyzed descriptively to provide an overview of students cognitive learning outcomes including students absorption and learning effectiveness on indication of global warming material. The research result obtained were the average of students absorption ability in the experimental class was 76,94% and 68,33% for control class. Thus, can be concluded that the implementation of the concept attainment learning model was effective to increase student cognitive learning outcomes in SMA Negeri 9 Pekanbaru on the subject of global warming.